Partial substitution of manure reduces nitrous oxide emission with maintained yield in a winter wheat crop. (15th January 2023) - Gao, Huizhou; Xi, Yajing; Wu, Xueping; Pei, Xuexia; Liang, Guopeng; Bai, Ju; Song, Xiaojun; Zhang, Meiling; Liu, Xiaotong; Han, Zixuan; Zhao, Gang; Li, Shengping
Abstract: Conventional fertilization of agricultural soils results in increased N2 O emissions. As an alternative, the partial substitution of organic fertilizer may help to regulate N2 O emissions. However, studies assessing the effects of partial substitution of organic fertilizer on both N2 O emissions and yield stability are currently limited. We conducted a field experiment from 2017 to 2021 with six fertilizer regimes to examine the effects of partial substitution of manure on N2 O emissions and yield stability. The tested fertilizer regimes, were CK (no fertilizer), CF (chemical fertilizer alone, N 300 kg ha −1, P2 O5 150 kg ha −1, K2 O 90 kg ha −1 ), CF + M (chemical fertilizer + organic manure), CFR (chemical fertilizer reduction, N 225 kg ha −1, P2 O5 135 kg ha −1, K2 O 75 kg ha −1 ), CFR + M (chemical fertilizer reduction + organic manure), and organic manure alone (M). Our results indicate that soil N2 O emissions are primarily regulated by soil mineral N content in arid and semi-arid regions. Compared with CF, N2 O emissions in the CF + M, CFR, CFR + M, and M treatments decreased by 16.8%, 23.9%, 42.0%, and 39.4%, respectively. The highest winter wheat yields were observed in CF, followed by CF + M, CFR, and CFR + M. However, the CFR + M treatment exhibited lower N2 O emissions while maintaining high yield, compared with CF. Four consecutive years of yield data from 2017 to 2021 illustrated that a single application of organic fertilizer resulted in poor yield stability and that partial substitution of organic fertilizer resulted in the greatest yield stability. Overall, partial substitution of manure reduced N2 O emissions while maintaining yield stability compared with the synthetic fertilizer treatment during the wheat growing season. Therefore, partial substitution of manure can be recommended as an optimal N fertilization regime for alleviating N2 O emissions and contributing to food security in arid and semi-arid regions. Graphical abstract: Image 1 Highlights: Soil N2 O emissions were mainly regulated by soil mineral N content in arid and semi-arid regions. Chemical fertilizer results in higher N2 O emissions than does the application of organic fertilizer containing the same amount of N. Partial substitution of organic fertilizer allowed for mitigating N2 O emissions while simultaneously maintaining crop outputs. Partial substitution of organic fertilizer has the greatest yield stability.